Kesetaraan Gender dalam Inklusi Keuangan Keluarga - Latifah, Eny (PSGA Institut Agama Islam Tarbiyatut Tholabah, 2023)
The issue of gender equality has existed for a long time. In fulfilling family needs it is often seen that men are still the main actors and women are the supporters or substitutes. From this phenomenon, we can see later how far gender equality will be seen in meeting family needs. This type of literature research aims to find out the roles of women and men in family financial inclusion and gender equality in family financial inclusion. The study results are that the roles of women and men today are very balanced and symbiotic and complementary in fulfilling family inclusion. Gender equality in family inclusion today is very visible with the symbiotic roles of women and men in fulfilling family needs and complementary in the role of family financial inclusion to realize the needs of a harmonious family.